Promotion Guidelines of the Morale for Job Performance of Teachers Under Phetchabun Secondary Educational Service - Jaisean, Thanita (Academic MCU Buriram Journal, 2024)
The purposes of this research were to study and find the guidelines for promotion of teacher’s morale in job performance. The research was conducted into 2 steps: 1) studied the state of teacher’s morale in job performance. The sample consisted of 322 teachers obtained by using Krejcie & Morgan formula and simple random sampling. The study instrument was a questionnaire concerning the teacher’s morale in job performance with the validity between 0.67 - 1.00 and the reliability at 0.98. Data were analyzed by mean and standard deviation. 2) the found the guidelines for promotion of teacher’s morale in job performance was conducted by the discussion group comprising 7 experts. The instrument was the recording form of discussion group. Data was analyzed by content analysis. The research result found that: 1. The state of teacher’s morale in job performance in overall was at the high level. To considered in each aspect, it was found that the highest mean was the respect from other people, followed by the relationships with administrators and the lowest mean was the job. 2. The guidelines for the guidelines for promotion of teacher’s morale in job performance were as follows: 1) The aspect of career stability should set the criteria and consider results based on efficiency and success of the work, 2) the aspect of respect from other people should encourage workmate to exchange knowledge together and encourage personnel to submit work according to their knowledge and abilities, 3) the aspect of job description should assign work according to knowledge, ability, and aptitude, and set the standards for performance according to goals, 4) the aspect of career advancement should encourage teachers to transfer knowledge to outside agencies, 5) the aspect of relationships with administrators should provide opportunities for teachers to participate in planning, set a mutual agreement for work and the administrators must listen to teachers’ opinions and suggestions, 6) the aspect of working environment should provide adequate and appropriate facilities and adjust the environment to be safe and 7) the aspect of co-workers should encourage teachers to have a professional learning community to take care of each other, share and respect each other.